Streambank Erosion Susceptibility Index and Flood-prone Area Mapping along the Karra River, Hetauda, Central Nepal Sub-Himalaya - Rai, Rythum; Tamrakar, Naresh Kazi (Transactions on Engineering and Computing Sciences, 2020)
The Karra River, one of the major tributaries of the Rapati River, is the 5th order stream that extends for about 21.91 km length in 92 sq. km. of watershed area. It is situated in the southern region of the Hetauda City, which is under the rapid development as a settlement and industrial area. The Karra River area is frequently impacted by streambank erosion and flooding during the heavy rainfall in monsoon due to loosely consolidated sedimentary terrain of the Upper Siwalik Subgroup and the unconsolidated Late Quaternary Deposits, which are vulnerable to erosion. Morpho-hydraulic parameters and stream cross-sectional characteristics and parameters of streambank erosion susceptibility index (SESI) rating system were assessed along the Karra River at 19 transects. The rating of the SESI are based on bank angle, bank height ratio, root depth ratio, root density, surface protection, bank materials and characteristics of stratification. The flood-prone area map was prepared based on the morpho-hydraulic parameters of the stream based on the maximum bankfull depth. The ER and W/D ratio were estimated to determine the affinity of flooding and lateral instability of the stream. Near Bank Stress Index and SESI dealt with streambank erosion potential were assessed to estimate the streambank erosion rate.